The impact of marketing auditing on employee’s commitment with marketing ethics in Jordanian Five star Hotels - Tareq N. , Hashem (2013)
The study aims to investigate the impact of marketing auditing on employee’s commitment with marketing ethics in Jordanian Five star Hotels. The study population consisted of Jordanian Five stars Hotels employees. A questionnaire was distributed over a convenience sample amounting 200. 125 questionnaires were collected, that is (62.5%) of the total sample. The study results indicated that marketing auditing has positive impact on employee’s commitment with marketing ethics in Jordanian Five star Hotels. There are significant differences in marketing auditing impact on employee’s obligations with marketing ethics in Jordanian Five star Hotels due to gender, academic qualification and experience.